Micromechanical modeling of polyamide-based hybrid nanocomposite reinforced with PZT piezoelectric particles and carbon nanotubes - Min Wan; Ao Su; Guangjie Han; Zixuan Zhang; Tao Zhang (Journal of Engineering and Applied Science)
Abstract This exploration presents a micromechanical analysis of a hybrid nanocomposite comprising spherical lead zirconate titanate (PZT) piezoelectric particles and haphazardly oriented carbon nanotubes (CNTs) embedded within a polyamide matrix. Employing the Mori–Tanaka framework, a two-step modeling approach was created to examine the coupled elastic and piezoelectric properties of the composite. The model explicitly accounts for both uniform distribution and aggregation phenomena of CNTs, reflecting realistic microstructural conditions. Outcomes demonstrate that PZT particles predominantly enhance the piezoelectric response and contribute to increased stiffness, while uniformly dispersed CNTs significantly improve the mechanical attributes, including Young’s and shear moduli. Conversely, CNT aggregation adversely affects both mechanical and piezoelectric traits owing to reduced interfacial effectiveness. Validation against experimental data and literature confirms the accuracy of the model. These outcomes emphasize the importance of distribution control in nanocomposites and provide insights into the design of advanced multifunctional materials. The study paves the way for future research into optimizing nanoparticle distribution techniques and expanding the application of hybrid piezoelectric composites in industrial and environmental monitoring systems.